Media and the Politics of Offence
XI, 258 p. 8 illus., 7 illus. in color.
Keywords: This book explores different forms of mediated offence in the context of Trump's America, Brexit Britain, and the rise of far-right movements across the globe. In this political landscape, the so-called ‘right to offend’ is often seen as a legitimate weapon against a ‘political correctness gone mad’ that stifles ‘free speech’. Against the backdrop of these current developments, this book aims to generate a productive dialogue among scholars working in a variety of intellectual disciplines, geographical locations and methodological traditions. The contributors share a concern about the complex and ambiguous nature of offence as well as about the different ways in which this so-called ‘negative affect’ comes to matter in our everyday and socio-political lives. Through a series of instructive case studies of recent media provocations, the authors illustrate how being offended is more than an individual feeling and is, instead, closely tied to political structures and power relations.